2020
DOI: 10.3389/fbioe.2020.00966
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Soft and Passive Assistive Device to Lower the Metabolic Cost of Sit-to-Stand

Abstract: Various assistive devices like exoskeletons have been developed to aid the growing number of disabled people. Recent studies have started to explore using soft rather than rigid components to create lightweight and unobtrusive systems that can be more easily adopted by the general population. However, there is a tradeoff between compliance and power in these systems. We investigated the physiological benefits of using an inconspicuous, soft and passive assistive device which would avoid bulkiness, heaviness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Granados et at. [74] and Lee et al [75] designed a sit-to-stand device for elderly and spinal-injured people by combining gait trainers and partial weight-bearing lifters. There are also reported works of passive upper limb supporters for sanding operation [76], pneumatic muscleactuating arms [77], arm supporters [78], walking protection [79] and other exoskeletons [80].…”
Section: B Synthetic Passive Exoskeletonsmentioning
confidence: 99%
“…Granados et at. [74] and Lee et al [75] designed a sit-to-stand device for elderly and spinal-injured people by combining gait trainers and partial weight-bearing lifters. There are also reported works of passive upper limb supporters for sanding operation [76], pneumatic muscleactuating arms [77], arm supporters [78], walking protection [79] and other exoskeletons [80].…”
Section: B Synthetic Passive Exoskeletonsmentioning
confidence: 99%
“…Passive components [34][35][36][37] are often used in gait rehabilitation to reduce the energy costs of task-specific [38] elements of everyday life such as walking [39], running [40], and the sit-to-stand transfer [41]. Regardless of pathology or injury, the restoration of efficient gait has been extensively researched.…”
Section: Discussionmentioning
confidence: 99%
“…Gams et al (2013) showed the exoskeleton significantly reduced metabolic power during five minutes of repeated squatting, and Kim et al (2013) found reductions in integrated EMG during sit-to-stand and squatting with loads up to 26 kg. One study presented unclear results for a passive knee extension-assist soft exosuit during 5 minutes of repeat sit-to-stand, with a statistically significant 3.2% reduction in metabolic power, no significant difference in RPE (despite a slight average reduction), and no consistent patterns in results for anaerobic threshold or EMG data (Lee, Kim, and Park 2020).…”
Section: Summary Of Evidence Extracted For Exoskeletons To Assist Sta...mentioning
confidence: 99%